The evolution of cost-productivity and efficiency among US credit unions - Wheelock, David C.; Wilson, Paul W. (Journal of Banking & Finance, 2013)
Advances in information-processing technology have eroded the advantages of small scale and proximity to customers that traditionally enabled small lenders to thrive. Nonetheless, the membership and market share of US credit unions have increased, though their average size has also risen. We investigate changes in the efficiency and productivity of US credit unions during 1989–2006 by benchmarking the performance of individual firms against an estimated order-α quantile lying “near” the efficient frontier. We construct a cost analog of the Malmquist productivity index, which we decompose to estimate changes in cost and scale efficiency, and changes in technology. We find that cost-productivity fell on average across all credit unions but especially among smaller credit unions. Smaller credit unions confronted a shift in technology that increased the minimum cost required to produce given amounts of output. All but the largest credit unions also became less scale efficient over time.